Um ambiente para especificação e execução AD-HOC de processos de negócio baseados em serviços Web - Mendes Júnior, José Reginaldo de Sousa (2008)
Recently the focus given to Web Services and Semantic Web technologies has provided the development of several research projects in different ways to addressing the Web services composition issue. Meanwhile, the challenge of creating an environment that provides the specification of an abstract business process and that it is automatically implemented by a composite service in a dynamic way is considered a currently open problem. WSDL and BPEL provided by industry support only manual service composition because they lack needed semantics so that Web services are discovered, selected and combined by software agents. Services ontology provided by Semantic Web enriches the syntactic descriptions of Web services to facilitate the automation of tasks, such as discovery and composition. This work presents an environment for specifying and ad-hoc executing Web services-based business processes, named WebFlowAH. The WebFlowAH employs common domain ontology to describe both Web services and business processes. It allows processes specification in terms of users goals or desires that are expressed based on the concepts of such common domain ontology. This approach allows processes to be specified in an abstract high level way, unburdening the user from the underline details needed to effectively run the process workflow